1999
DOI: 10.7863/jum.1999.18.4.295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ocular arterial changes in glaucoma with color Doppler ultrasonography.

Abstract: The purpose of this study was to evaluate hemodynamic changes of the retrobulbar vasculature caused by different intraocular pressures with color Doppler ultrasonography. Fifty normal eyes in 25 patients, 13 patients with normal tension glaucoma, and 19 patients with acute glaucoma and increased intraocular pressure (greater than 30 mm Hg) were enrolled in this study. In 15 of 19 patients with acute glaucoma patients, follow-up color Doppler ultrasonography was also undertaken after laser peripheral iridectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 18 publications
2
21
1
2
Order By: Relevance
“…These differences were observed in the absence of differences in IOP, diabetes, systemic blood pressure and heart disease between the groups. Our results are consistent with previous studies in which reduced ocular blood flow velocities in the retrobulbar blood vessels have been reported in patients with POAG compared to controls; this finding has been reported in cohorts of ED [40][41][42] and of AD. 43 In addition, Siesky et al 31 reported lower blood flow values in all retrobulbar blood vessels in POAG patients of AD compared to those of ED.…”
Section: Discussionsupporting
confidence: 83%
“…These differences were observed in the absence of differences in IOP, diabetes, systemic blood pressure and heart disease between the groups. Our results are consistent with previous studies in which reduced ocular blood flow velocities in the retrobulbar blood vessels have been reported in patients with POAG compared to controls; this finding has been reported in cohorts of ED [40][41][42] and of AD. 43 In addition, Siesky et al 31 reported lower blood flow values in all retrobulbar blood vessels in POAG patients of AD compared to those of ED.…”
Section: Discussionsupporting
confidence: 83%
“…The blood velocities in the retrobulbar arteries vary with the individual’s age, systemic blood pressure, smoking habit and IOP [72, 73, 74]. It has been demonstrated that a significant increase in the RI and pulsatility index of the CRA, medial and lateral short posterior ciliary artery in patients with acute glaucoma returned to normal after therapy to normalize the IOP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that a significant increase in the RI and pulsatility index of the CRA, medial and lateral short posterior ciliary artery in patients with acute glaucoma returned to normal after therapy to normalize the IOP. It has been suggested that acute elevations of IOP might decrease the blood supply to the optic disc [74]. A decrease in the RI, which generally reflects vascular bed resistance, was observed after surgically reducing IOP in patients with chronic glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Its clinical use in ophthalmology, however, has not been as widespread as the Pourcelot index or resistive index (RI), with few studies determining its significance in glaucoma. Two studies Disturbed correlation between arterial resistance and pulsatility in glaucoma patients failed to identify differences in PI between healthy individuals and primary open-angle glaucoma (POAG) (Januleviciene et al 2008) or normal tension glaucoma (NTG) (Chiou et al 1999). In both cases, no further analysis was made to test how PI could relate to other variables.…”
Section: Introductionmentioning
confidence: 99%